Preliminary study on the effects of movement velocity training of the upper limbs on gait ability in older adults: a nonrandomized controlled trial - Yamamoto S (Dove Medical Press, 2019)
Saki Yamamoto,1 Akira Iwata,1 Yuki Yano,1 Toshimitsu Ohmine,1 Keisuke Honma,1 Kazuma Senzaki,1 Minami Fujiwara,1 Takayuki Murakami,1 Junji Inoue,1 Yuki Sano,2 Shuji Okagawa,3 Yuta Otsuki,4 Hideyuki Wanaka,5 Masataka Kataoka,1 Hiroshi Iwata61Department of Physical Therapy, Faculty of Comprehensive Rehabilitation, Osaka Prefecture University, Habikino, Osaka, Japan; 2Department of Rehabilitation, Osaka General Medical Center, Osaka, Osaka, Japan; 3Department of Rehabilitation, Tatsumi Hospital, Ikeda, Osaka, Japan; 4Department of Rehabilitation, Kisei Hospital, Osaka, Osaka, Japan; 5Department of Rehabilitation, Kobe Rosai Hospital, Kobe, Hyogo, Japan; 6Department of Cardiovascular Medicine, Juntendo University Graduate School of Medicine, Bunkyo-ku, Tokyo, JapanPurpose: Movement velocity of the limbs or trunk plays an important determinant of gait speed in older adults. Movement velocity-focused training of the lower limbs or trunk has recently been shown to be an effective intervention to improve gait ability. Because movement velocities of various body regions are significantly correlated, movement velocity training of the upper limbs may also be effective for improving gait speed. Therefore, the purpose of this study was to investigate whether movement velocity training of the upper limbs in a seated position is effective for improving gait ability.Patients and methods: This study was a nonrandomized controlled trial. The participants were older adults residing in geriatric health service facilities. They were assigned to the movement velocity training of the upper limbs group (n=26) or control group (n=15). The participants in the training group performed exercises (three times per week for 10 weeks) to move the upper limbs as quickly as possible. The outcomes were gait speed, movement velocity, and quadriceps strength. These measurements were performed preintervention and 4, 8, and 10 weeks after intervention.Results: A significant time–group interaction was found for maximum gait speed and movement velocity of the upper limbs. Bonferroni post-hoc test showed significant improvement in gait speed between preintervention and 10 weeks after intervention in the training group. The movement velocity of the upper limbs was significantly improved between preintervention and 4, 8, and 10 weeks after intervention.Conclusion: Movement velocity training of the upper limbs showed significant and clinically relevant improvements in maximum gait speed at 10 weeks after intervention. This training is a potentially useful intervention and can be safely performed.Keywords: older people, movement velocity training, arm, gait speed, seated position